Pendampingan Manajemen Pengelolaan Kelas pada RA Al-Hamidiyah Pangkalan Pangandaran - Abidin, Jenal; Masitoh, Imas; Wahyuni, Ai Teti; Eryani, Esa; Aliyah, Fitria Himatul (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Classroom management is very important in the learning process. Because a comfortable classroom atmosphere can make the learning process conducive and enjoyable, especially at the early childhood education level. The purpose of this research is to find out and describe how classroom management at RA Al-Hamidiyah Pangkalan Pangandaran also makes RA Al-Hamidiyah Pangkalan Pangandaran a model of classroom management that can be used as an example in good classroom management. The method that researchers take is a service learning method. The results obtained from this research are that classroom management at RA Al-Hamidiyah Pangkalan Pangandaran went very well. The importance of good classroom management because it is the main factor that can create a conducive, fun and effective classroom atmosphere has a major influence on the ongoing learning process in the classroom.